Peripheral artery disease impairs myocardial perfusion through increasing pulse wave reflection: the Northern Shanghai study. (25th November 2020) - Yu, S; Teliewubai, J; Fan, X; Chi, C; Ji, H; Blacher, J; Zhang, Y; Xu, Y
Abstract: Background: Peripheral artery disease (PAD) is prevalent and substantially contributes to cardiovascular mortality particularly in the elderly, although the pathophysiological impact of PAD on heart itself still needs further investigation. In theory, PAD can increase pulse wave reflection which is an important determinant of subendocardial viability ratio (SEVR), a valuable estimate of myocardial perfusion as indicated by previous invasive studies. Thus, we hypothesize that PAD impairs myocardial perfusion through increasing pulse wave reflection. In this study, we aim to test this hypothesis in a large cohort from the Northern Shanghai Study. Methods: A total of 2947 community-dwelling elderly Chinese (43.6% male, mean age: 71.3±5.9 years) were recruited. Ankle-brachial index were measured with the VP1000 device and used to diagnose PAD. Pulse wave reflection was estimated as aortic augmentation pressure (AP). Aortic BP, AP and SEVR were assessed by radial applanation tonometry. Multiple linear regression with SEVR and AP as dependent variable and PAD as independent variable, meanwhile adjusted for other covariates, were performed, respectively. Results: 375 (12.7%) participants presented PAD. Compared to subjects without PAD, those with PAD showed significantly lower SEVR (126 vs. 132, P<0.001) but higher AP (19 vs. 17 mmHg, P<0.001). Multiple regression analysis revealed that both SEVR (regression coefficient [B] = −1.69, P=0.04, R2=0.61) and AP (B=1.19, P=0.04, R2=0.56) significantly associated with PAD, respectively. However, the association between SEVR and PAD was abolished when further adjusted for AP (B=−0.49, P=0.52). Similar results were obtained when inter-leg systolic BP difference was used to diagnose PAD. Conclusions: PAD significantly and independently associates with myocardial perfusion; moreover, this association is mediated by increased pulse wave reflection. These findings provide a new dimension for understanding the pathophysiological mechanisms of cardiac damage of PAD. Funding Acknowledgement: Type of funding source: None